TEACHER’S FEEDBACK ON STUDENTS’ DESCRIPTIVE TEXTS - Indri EKa Pertiwi (Journal of English and Education, 2013)
This study intends to investigate the way of teacher in providing feedback for students’ descriptive texts, and examine the responses of the students toward the given feedback. It employed a descriptive case study, involving an English teacher who taught twenty students as the respondents. The data were gathered from classroom observations, questionnaires, and interviews. The obtained data were mainly analyzed based on Hedge (1988), Kaplan Grabe (1996), Ferris (2002) and Hyland (2003) explaining forms of feedback. The findings showed that the teacher provided four forms of feedback as proposed by Hedge et al (1988); whole class conference, one-on-one conference, commentary, and minimal marking. Most students tended to respond positively toward the feedback provided by the teacher and they considered it helpful for them to write better. In conclusion, feedback from teacher is an essential aspect for students in helping them make better writing. However, for the sake of clarity and understanding, it is also important to pay attention to the forms of feedback given. Keywords: Feedback, Writing, Descriptive Texts, Junior High School